SIMPLE FORMS OF ZIRCON CRYSTALS FROM CRYSTALLINE ROCKS OF THE UKRAINIAN SHIELD AND THEIR MORPHOLOGICAL TYPES
The main basics in geometric crystallography of zircon, developed by many researchers in the 18th - 20th centuries, are briefly described. The data of goniometric study of zircon from crystalline rocks of the Ukrainian Shield (USh) are summarized. They cover zircon predominantly from granites and alkaline rocks of most the USh megablocks. The set of habit simple forms on zircon crystals is small: 111, 110, 100, 221, 331 and 311. These forms define two contrasting habits of zircon crystals - prismatic and dipyramidal. Among the prismatic crystals several main morphological types of crystals are distinguished: 110 + 111 – zircon type, 100 + 111 – hyacinth type, 110 +100